Binahong leaf extract (anredera cordifolia) mucoadhesive patch as an alternative therapy for recurrent aphthous stomatitis - Lisa Oktaviona Saputri; Dania Tamimmi; Renita Rahma Chairu Nisa; Nabila Hardina Rossah; Afsal Unnisa Rachman; Yuanita Lely Rachmawati (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Recurrent Aphthous Stomatitis (RAS) is one of the most common oral diseases of all ages. There has been no study that defines the leading cause of RAS. The utilization of binahong leaves (Anredera cordifolia) can be beneficial for the treatment of RAS as it acts as an anti-inflammatory and accelerates the proliferation of fibroblasts. The combination between binahong leaves and the mucoadhesive patch will increase the effectiveness of RAS treatment.Method: Literature study through PubMed and Google Scholar databases was conducted using PRISMA flow chart looking for the efficacy of binahong leaves (Anredera cordifolia) for mucosa wound healing and mucoadhesive patches for the treatment of RAS.Result: The search results found 31 articles that met the criteria for analysis. Flavonoids and saponins in binahong leaves extract act as an anti-inflammatory and increase the proliferation of wound healing. Mucoadhesive patch formulation can increase the effectiveness of RAS treatment on the mucosa.Conclusion: Binahong leaves extract in the form of mucoadhesive patches can be used as an alternative treatment for Recurrent Aphthous Stomatitis.